Fournier’s gangrene in a female: A case report - Rabbia Zubair; Asia Mohammad Azam; Munqabat Fatima; Mariam Muhammad Azam; Aresha Masood Shah; Muhammad Ahsan Rehman Khan; Úzair Yaqoob (SAGE Open Medical Case Reports, 2024)
Fournier’s gangrene is characterized by an acute necrotic infection. The infection can occur in all parts of the body including the scrotum, penis, or perineum, and is a rare condition that is primarily reported in men and seldom in women. Existing literature suggests that it might be underreported, possibly leading to overlooked cases. Risk factors include diabetes, chronic illness, and trauma. This case involves a 52-year-old female with a 10-year medical history of diabetes mellitus, multiple healed skin lesions all over the body, and dermatitis. The presentation was a perianal swelling, which progressed into an extensive necrotizing soft tissue infection of the perineum, making a diagnosis of Fournier’s gangrene. She underwent wide local debridement and was managed with antibiotics in a timely manner. The patient’s clinical course and subsequent follow-up were uneventful. Uncontrolled diabetes and dermatitis significantly increase the risk of Fournier’s gangrene; therefore, it should be suspected in women with such comorbid conditions. This case highlights the need for increased awareness and vigilance regarding this condition among women.